Towards performance evaluation of cloud service providers for cloud data security. Issue 4 (August 2016) - Ramachandran, Muthu; Chang, Victor
Highlights: We have ciritcally evaluated cloud service providers business processes on cloud data security. We have also evaluated cloud computing adoption framework (CCAF). We have developed cloud data security models based on Business Process Modelling Notations (BPMN). We have conducted BPMN simulation for CSP-1 & CSP-3 and the results can reveal performances issues related to data security as part of any organizations initiative on Business Process Management (BPM). Abstract: Today's data is sensitive that requires privacy and security both from the cloud service providers (CSP) as well as from users in its all the form of data states: data at rest, while transferring data, enquiring data, and processing the data. Cloud computing has been applied in the health sector, national security services, banking and other business and companies that store confidential data into the cloud as we have seen in recent years. Therefore, information and data security is a crucial issue that needs to be addressed thoroughly in the cloud computing business. This research deals with the performance analysis of recent cloud data security models. This paper proposes cloud data security models based on Business Process Modeling Notations (BPMN) and simulation results can reveal performances issues related to data security as part of any organizations initiative on Business process management (BPM).